2012
DOI: 10.1590/s0044-59672012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of sand flies in domiciliary environment of Santarém, state of Pará, Brazil: species composition and abundance patterns in rural and urban areas

Abstract: This paper aimed to evaluate the richness, abundance and frequency of sand fly occurrence in rural and urban areas American visceral leishmaniasis -AVL is endemic in the study area of Santarém municipality, Pará state. Sand flies were collected during 1995-2000, using CDC light traps placed in neighborhoods and rural areas of the municipality. A total of 53.454 individuals and 26 species of sand flies were collected. The most abundant species in both urban and rural environments was Lutzomyia longipalpis, vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
3
6
0
3
Order By: Relevance
“…Our finding of low genetic diversity among individuals which were caught from periurban areas, is consistent with similar patterns of low genetic diversity among urban sand fly populations (Shannon Index ranged from 0.08 to 0.34) as revealed by Feitosa et al [37]. It has been suggested that differential adaptation to changes in urban environments and urbanized habitat simplification is related to reduction in genetic variability, as noticed in genetic studies of urban mosquito populations [38] and cricket species [39].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding of low genetic diversity among individuals which were caught from periurban areas, is consistent with similar patterns of low genetic diversity among urban sand fly populations (Shannon Index ranged from 0.08 to 0.34) as revealed by Feitosa et al [37]. It has been suggested that differential adaptation to changes in urban environments and urbanized habitat simplification is related to reduction in genetic variability, as noticed in genetic studies of urban mosquito populations [38] and cricket species [39].…”
Section: Discussionsupporting
confidence: 91%
“…Compared to other villages evaluated in the study, Riacho do Brejo showed a greater variety of animal enclosures, such as pens for chickens, pigs, and dogs, as well as fruit trees such as banana and guava trees, providing excellent conditions for phlebotomine reproduction and population growth 37,38 . Brejo do Mata Fome was much more artificially modified and showed the lowest population density and lowest sand fly faunal diversity, corroborating the previous results of Feitosa et al 39 . The interference of climatic factors with the sand fly population has been studied previously.…”
Section: Discussionsupporting
confidence: 90%
“…Deane & Deane (1937) have reported human cases of American visceral leishmaniasis in Pará, Brazil. From 1995-2000, Feitosa et al (2012 identified phlebotomine species in rural and urban sites in Santarém, Pará, and the vector Lutzomyia longipalpis was abundant.…”
Section: Introductionmentioning
confidence: 99%
“…Deane & Deane (1937) have reported human cases of American visceral leishmaniasis in Pará, Brazil. From 1995-2000, Feitosa et al (2012 identified phlebotomine species in rural and urban sites in Santarém, Pará, and the vector Lutzomyia longipalpis was abundant.The city of Belém is an area of sporadic transmission of visceral leishmaniasis according to the Brazilian Ministry of Health (BRASIL, 2007). An entomological study conducted between 2009 and 2011 identified six species of epidemiologically important vectors for the transmission of cutaneous leishmaniasis in that region (FERREIRA et al, 2014).…”
mentioning
confidence: 99%